Do Women Find the Progesterone Vaginal Ring Acceptable? Findings from Kenya, Nigeria, and Senegal. Issue 1 (2nd February 2018) - RamaRao, Saumya; Obare, Francis; Ishaku, Salisu; Mané, Babacar; Clark, Heather; Liambila, Wilson; Unumeri, Godwin; Birungi, Harriet; Diop, Nafissatou; Rajamani, Deepa; Townsend, John
Abstract: The progesterone vaginal ring (PVR) is a contraceptive designed for use by breastfeeding women in the first year postpartum. This Report presents results of an acceptability study of the PVR in Kenya, Nigeria, and Senegal. Women seeking postpartum family planning services were offered various contraceptive options including the PVR. Of the 174 participating women, 110 (63 percent) used one ring and 94 (54 percent) completed the study by using two rings over a six‐month period. Women were interviewed up to three times: at the time they entered the study, at 3 months (the end of the first ring cycle), and at 6 months (the end of the second ring cycle or when they exited if they had discontinued earlier). Many participants found the ring to be acceptable, with over three‐quarters reporting that it was easy to insert, remove, and reinsert. While a small proportion of women experienced ring expulsion, the majority did not. These findings suggest that even in countries with little or no use of vaginal health products, contraceptive vaginal rings offer women a new option that they are able and willing to use.